This sceptred isle twentieth century - Lee, Christopher (BBC, 1999)
Christopher Lee's seminal history series, which accompanied the award-winning BBC radio series, narrates the rich and gripping story of Britain, from the Roman Invasion in 55 BC to the dawn of the 21st century. In this volume, the author looks at Britain from the death of Queen Victoria in 1901 up to the present day. The text covers the century's major political and economic events, as well as the scientific and cultural changes that have influenced the day-to-day lives of British people.